A case of early localized scleroderma that was manifested as a port-wine stain - Meng, Qinqin; Guo, Meiliang; Yuan, Dingfen; Deng, Hui (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Port-wine stain (PWS) and localized scleroderma (LS) are easy to be identified in the late stage of diseases. However, several reports of early morphea present an early underrecognized inflammation that resembles PWS. This case was presented to highlight the early diagnosis of LS, which manifests as PWS. Misdiagnosis can delay the diagnosis of scleroderma and cause some other serious complications.